The Effect of Pilates Training on Isoprostane, Fasting Glucose and Body Composition in Women with Breast Cancer - Sara Zandi; Saeedeh Shadmehri; Nasibe Kazemi (Islamic Azad University, 2016)
Introduction: Addressing physical activities is one of the important pillars of the health management of patients with breast cancer. The purpose of this study was to investigate the effect of Pilates training on isoprostane, fasting glucose and body composition in women with breast cancer. Methods: In this quasi-experimental study, 24 women with breast cancer who referred to health and therapy centers and private clinics of Shiraz were selected and divided into two groups: Pilates training and control. Pilates training group performed exercises for 10 weeks, 3 sessions per week and 60 minutes each session. The control group performed only their daily activities during this period. Blood sampling and physical examination were performed before and after the training period. For statistical analysis of data Kolmogorov- Smirnov, paired sample t-test and independent sample t- tests (p≤0.05) were used. Results: The results showed that ten weeks of pilates training had no significant effect on isoprostane (p=0.35), weight (p=0.09), body mass index (p=0.09) and WHR (p=0.07) in women with breast cancer. Also, Pilates training had a significant effect on the reduction of fasting glucose (p=0.03) in women with breast cancer. Conclusion: According to the findings of the present study, although 10-week Pilates training are not effective in improving the isoprostane and body composition of women with breast cancer, it can improve the fasting glucose in these patients.